1990
DOI: 10.1128/aac.34.5.844
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a glutathione S-transferase that mediates fosfomycin resistance in bacteria

Abstract: The enzyme that modifies fosfomycin by formation of an adduct with glutathione was purified 12-fold with a 56% activity yield by passage through DEAE Sephacel and high-performance liquid chromatography molecular exclusion columns. Its functional form was a homodimer of two 16,000-dalton polypeptides, which possibly showed an antiparallel a tertiary structure and which lacked marked hydrophobic regions. Visualization of the reaction was achieved by precolunm derivatization of glutathione and the adduct, separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 27 publications
1
58
0
3
Order By: Relevance
“…In the past, GST had been characterized in eukaryotes as a detoxifying enzyme. However, several recent reports concerning bacterial GSTs have appeared (1,13,24). It has been shown that GST plays a role in the assimilation of dichloromethane in Methylobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, GST had been characterized in eukaryotes as a detoxifying enzyme. However, several recent reports concerning bacterial GSTs have appeared (1,13,24). It has been shown that GST plays a role in the assimilation of dichloromethane in Methylobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…FosA (glutathione S-transferase), the first to be described (in 1988), is a metalloenzyme transferred through plasmids in Enterobacteriaceae. It catalyzes the reaction between glutathione and fosfomycin to an inactive adduct (102,(105)(106)(107). New subtypes, with similar structure, of the gene have been described (fosA2, fosA3, fosA4, and fosA5) (108)(109)(110).…”
Section: Acquired Resistancementioning
confidence: 99%
“…Defects in one or both of the transport systems (caused by mutations in the uhpT and glpT structural genes or the regulators) can confer fosfomycin resistance (17,18,31). In addition, plasmid-encoded fosfomycin resistance conferred by an enzyme that inactivates the antibiotic has been described (3)(4)(5).…”
mentioning
confidence: 99%